The Directors Remuneration and Firm Performance in Property and Construction Industries Listed on Bursa Malaysia’s Main Board - Mohd Razali, Mohd Waliuddin; Fenny Ester, Joslin; Noraisyah, Abd Rahman; Akmal Hisham, Tak (EPH, 2018)
Nowadays, directors’ remuneration has become increasingly popular and being discussed by all walks of life. Through a holistic approach based on corporate governance best practice, it could affect the internal and external performance of corporate in terms of management and financial performance. The main objective of the study is to investigate the directors’ remuneration listed under property and construction industry towards firm performance. 266 samples of annual reports of listed firms for the period of 2013 to 2015 were obtained and examined. The regression results show that directors’ remunerations have significantly positive relationship with firm performance. Appealing remuneration package encourages and attracts the directors who have the ability and potential in successfully managing the firm. Most of control variables have significant relationship with firm financial performance except CEO duality which does not have significant relationship with financial performance. Future studies could recommend using other performance measures such as Tobin’s Q or Economic Value Added (EVA) and the total directors’ remuneration could be broken up to several parts which could reveal new research insights.